Investigation of the relationship between adiponectin gene polymorphism (ADIPOQ SNP rs-266729) and obesity Patients / Basra-Iraqi - Mohammad Falih Hashim; Fatima Saiwan Sabah; Hamid Jaddoa Abas (College of Pharmacy University of Baghdad, 2024)
Adiponectin is one of the most important hormones secreted by adipose tissue and plays a major role in the development of obesity. A variant-specific ADIPOQ single nucleotide polymorphism (SNP rs-266729) with a C to G missense mutation can be strongly associated with obesity. Therefore, this study aims to evaluate the association of single nucleotide polymorphisms (SNP rs-266729) of the ADIPOQ gene with obesity and some biochemical markers in these patients. The case-control study included 186 participants (106 patients and 80 healthy control). DNA was extracted from whole blood and then the Restriction Fragment Length Polymorphism Polymerase Chain Reaction (RFLP-PCR) technique was used to limit the genotype of the ADIPOQ gene (rs266729) polymorphism. Also, the lipid profile, glycated hemoglobin (HbA1C), fasting blood glucose (FBG), insulin, and adiponectin were measured by standard methods. Results: The allele G in the ADIPOQ-gene polymorphism (rs266729) was a significantly higher frequency of 23 (21.6%) in the obese patients (P_Value = 0.039) compared with the control subject of 10 (12.5%). It significantly increased the risk in the additive model and allele frequency (P = 0.0139 and 0.0133), respectively. The rs266729 SNP showed a significant association with increased BMI, insulin, HOMO-IR, TG, VLDL, and lower adiponectin at a p-value of 0.001 for all, after adjustments for age and sex. Lower levels of high-density lipoprotein (HDL) were observed in the CG and GG genotypes compared to the ADIPOQ rs266729 SNP C.C genotype (p = 0.032). In obese individuals, there was no significant relationship between rs266729 SNP and HbA1C, FBS, TC, and LDL. In conclusion, the single nucleotide polymorphism (rs266729) of the ADIPOQ gene has a significant difference with BMI, insulin, TG, VLDL, and HOMO-IR in obese patients, which might be the cause of obesity.